Alternative Snack for Diabetic Patients from Sago (Metroxylon sp.) Starch and Tempe - Maya, Sofya; Sulaeman, Ahmad; Sinaga, Tiurma (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
This study aimed to develop food products made from sago starch (Metroxylon sp.) and tempe as alternative snacks for diabetics. This study used a completely randomized design (CRD) with two treatment ratios of sago starch to tempe, F1 (2:1) and F2 (1:1), and two replications for three products, namely puddings, muffins, and cookies. The organoleptic attributes of the products were evaluated by fourty semi-trained panelists. The results of the hedonic test showed that F2 was the formula selected for the puddings and muffins and that F1 was the formula selected for the cookies. The puddings had hardness of 83.47 gf, 92.28% water, 0.28% ash, 1.04% protein, 0.64% fat, 5.76% carbohydrate, 3.95% dietary fiber, and 0.81% resistant starch. The muffins had hardness of 3,861,87 gf, 56.18% water, 0.79% ash, 6.49% protein, 10.26% fat, 26.28% carbohydrate, 7.13% dietary fiber, and 3.59% resistant starch. The cookies had hardness of 1,655,02 gf, 5.05% water, 0.90% ash, 4.90% protein, 19.66% fat, 69.49% carbohydrate, 9.57% dietary fiber, and 6.00% resistant starch. These products contained different levels of dietary fiber and resistant starch. Puddings are categorized as a high-fiber food with a negligible level of resistant starch, the muffin as a high-fiber food with an intermediate level of resistant starch, and the cookie as a high-fiber food with a high level of resistant starch. In conclusion, these products had relatively high fiber content and need a further study to confirm the health benefits for glucose control in diabetics.